DIFFERENT APPROACHES TO THE DEVELOPMENT OF CHILDREN'S SPEECH - Egamberdiyev, Oyatillokh Alisher ugli; Maxamadjonov, Jakhongir Zokirjon ugli; Sobirova, Azizaxon Maribjon kizi (Educational Research in Universal Sciences, 2022)
Formation of different abilities of children is one of the most important issues in the modern education system. This includes the development of their speech activity. The article analyzes different approaches to the development of children's speech.